2003
DOI: 10.1152/ajpcell.00113.2003
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric modulation of a neuronal K+ channel by 1-alkanols is linked to a key residue in the activation gate

Abstract: Harris, Thanawath, Andrew R. Graber, and Manuel Covarrubias. Allosteric modulation of a neuronal K ϩ channel by 1-alkanols is linked to a key residue in the activation gate. Am J Physiol Cell Physiol 285: C788-C796, 2003; 10.1152/ajpcell.00113.2003.-The selective inhibition of neuronal Shaw2 K ϩ channels by 1-alkanols is conferred by the internal S4-S5 loop, a region that also contributes to the gating of voltage-gated K ϩ channels. Here, we applied alanine scanning mutagenesis to examine the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…To test whether other putative components of the Shaw2 activation machinery may also contribute to 1-alkanol binding, we applied alanine scanning mutagenesis to portions of S5 and S6 [27]. The S5 mutants exhibited normal or modestly altered function and modulation of the inhibition by 1-butanol.…”
Section: -Alkanol Action Involving the Main Activation Gate Of The Smentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether other putative components of the Shaw2 activation machinery may also contribute to 1-alkanol binding, we applied alanine scanning mutagenesis to portions of S5 and S6 [27]. The S5 mutants exhibited normal or modestly altered function and modulation of the inhibition by 1-butanol.…”
Section: -Alkanol Action Involving the Main Activation Gate Of The Smentioning
confidence: 99%
“…More significantly, however, as the alanine mutations approached the highly conserved Pro-Val-Pro-Val motif (PVPV), the inhibition by 1-butanol was progressively suppressed; and surprisingly, when the second proline of the PVPV motif was mutated to alanine (PVAV), 1-butanol induced a rapid reversible potentiation of the Shaw2 current. Further biophysical analyses indicated that destabilization of the closed state underlies this response [27]. Prolines in the PVPV motif may introduce a kink in the distal S6 helix, a segment that contributes to the main activation gate [36,38].…”
Section: -Alkanol Action Involving the Main Activation Gate Of The Smentioning
confidence: 99%
See 1 more Smart Citation
“…Currents were recorded 3-7 days postinjection. The Shaw2-F335A mutant was preferred for the experiments reported here because it exhibits higher expression levels and no significantly affected biophysical properties and inhibition by 1-alkanols (24). Patch-clamp recording was conducted as described previously (25) using an Axopatch 200B apparatus (Axon Instruments, Foster City, CA).…”
Section: Oocyte Injection and Electrophysiologymentioning
confidence: 99%
“…In these experiments, we used the strongly expressing mutant Shaw2-F335A whose electrophysiological properties and 1-alkanol sensitivity are similar to those of the wild-type channel (24). Throughout this report, we refer to Shaw2-F335A as Shaw2.…”
Section: The Inhibition Of Shaw2 Channels By 1-alkanols Exhibits Secomentioning
confidence: 99%